HYBRID MASCULINITY DALAM MUSIC VIDEO: Analisis Semiotika John Fiske pada Music Video Enhypen Sacrifice (Eat Me UP) - Reskiwardina, Andi; Unde, Andi Alimuddin; Sonni, Alem Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
Masculinity is homogeneously defined as a rule or rules in social practice and is represented by the culture depicted in a man. The majority of society demands that a man must be independent, strong, firm, tough, disciplined, think logically, able to be a protector and avoid anything related to women (no sissy stuff). However, along with the development of globalization and the proliferation of Korean wave fever among people around the world, K-Pop idols, especially men, have emerged bringing a new identity from the concept of masculinity called Hybrid Masculinity. This research aims to determine the form of Hybrid Masculinity in the music video Enhypen Sacrifice (Eat Me Up) using John Fiske's semiotic analysis with his theory The Codes of Television. The results of this research show that there are symbols and representations of a new form of male masculinity called Manufactured Versatile Masculinity and the discovery of new emphases in viewing the concept of masculinity itself.